Technological analysis of Tajamar obsidian of Quito - Falcón Revelo, Wilmer Isaac (Centro de Publicaciones Pontificia Universidad Católica del Ecuador, 2019)
This paper examines two non-consecutive occupations of the Tajamar site, located in Pomasqui, in the current city of Quito. Tajamar evidences a Formative occupation between 1191 - 850 cal. B.C., and an Integration occupation (600 - 1423 cal. A.D.). Both occupations present obsidian, a lithic material thathas been analyzed to understand the technology with which it was worked, the sources from whichthe obsidian was extracted, and its possible use. The two Tajamar occupations were examined withinthe archaeological perspective of operational chains and morpho-technological methodology. Thismethodology, in addition to allowing for more possibilities with respect to the material, can be comparedbetween sites and sets a precedent for future lithic studies in Ecuador. This research is a pertinentexample of the relationship that human beings have in an environment that culturally transformed andwhich also requires adaptive dynamics.